KONTRIBUSI KELENTUKAN PERGELANGAN TANGAN DAN KELINCAHAN TERHADAP HASIL SMASH BULU TANGKIS ESKTRAKURIKULER MTSN 1 BENGKALIS - Obie Alwin; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is that the smash technique in badminton, especially the lop smash, is less than optimal and ends up failing to get points. The purpose of this research was to see the contribution of wrist flexibility and agility to the MTs N 1 Bengkalis extracurricular badminton smash which was controlled by 12 samples using total sampling technique. The instruments in this research were wrist flexibility, shuttle run and forehand smash test. The data obtained from the analysis using the current product. Based on the analysis of the normality test data, X1 produces LoMax of 0.241 and Ltable 0.242 and X2 produces LoMax of 0.101 and Ltabel of 0.242. while variable Y produces LoMax of 0.139 and Ltabel of 0.242 This means LoMax <Ltable. Based on statistical data analysis, the data is normally distributed. Based on the analysis requirements test above, the hypothesis test on variables X1 and X2 on variable Y is data 0.812> 0.735 Rhitung> R table data.Thus, there is a contribution of wrist flexibility and agility to the results of extracurricular badminton smash MTs N 1 Bengkalis amounting to 65.93 %.Key Words: Wrist Flexibility, Agility, Forehand Smash